Supercritical Fluid Extraction with CO2 of Curcuma longa L. in Comparison to Conventional Solvent Extraction - Ann-Kathrin Widmann; Martin A. Wahl; Dietmar R. Kammerer; Rolf Daniels (MDPI AG, 2022)
Curcuma longa L. is a traditional medicinal and spice plant containing a variety of lipophilic active substances with promising therapeutic properties. In this work, the solvent properties of supercritical carbon dioxide in a pressure and temperature range of 75-425 bar and 35-75 °C were investigated when Curcuma longa rhizomes were extracted. The three main curcuminoids, namely curcumin, demethoxycurcumin, and bisdemethoxycurcumin, together with the three main constituents of the essential oil, i.e., ar-turmerone, α-turmerone, and β-turmerone, were analyzed in the resulting extracts. For statistical evaluation, experiments were performed employing a full factorial design, in which flow rate, extraction time, and drug load were kept constant. Within the given conditions, the experimental design revealed an optimum yield of all aforementioned substances, when supercritical carbon dioxide extraction was performed at 425 bar and 75 °C. For comparison, solvent extracts using methanol and n-hexane were prepared and their main components were characterized using LC-MS. The stability of the extracts was monitored upon storage for 6 months at 22 and 40 °C under protection from light. The decomposition of individual compounds was mainly observed in the presence of residual water in the extracts.